Self-Reward as a Modern Self-Care Strategy to Enhance Gen Z’s Psychological Well-Being: A Qualitative Case Study - Putri Nur Amalia (Istisyarah: Jurnal Bimbingan Konseling Islam, 2025)
Generation Z faces unprecedented psychological stress driven by complex academic and professional demands in a fast-paced digital era. Consequently, modern self-care strategies are vital to safeguard their mental health. This study aims to investigate how Generation Z utilizes self-reward as a contemporary self-care strategy to enhance their psychological well-being. Employing a qualitative case study design, this research examined two distinct Generation Z subjects within the same urban area: a university student (MS) and an employed professional (AS). Data were systematically analyzed using the interactive qualitative model of Miles, Huberman, and Saldaña. The findings reveal that self-reward modalities are highly contextual and phase-dependent. MS applies spontaneous, short-term rewards (e.g., entertainment, casual dining) as an immediate coping mechanism against academic burnout. Conversely, AS adopts structured, reflective rewards (e.g., travel, self-development workshops) to establish professional boundaries and maintain emotional stability. When practiced mindfully, self-reward effectively satisfies the core psychological needs of autonomy, competence, and relatedness, thereby reinforcing environmental mastery and self-acceptance. However, without self-regulation, it risks devolving into destructive consumptive behavior and task procrastination. This study concludes that mindful and proportional self-reward serves as a resilient, adaptive mechanism that harmonizes productivity with sustainable psychological well-being for the digital generation.